Female sexual dysfunction in patients with endometriosis: Indian scenario - Vineet V Mishra; Sakshi Nanda; Khushali Gandhi; Rohina Aggarwal; Sumesh Choudhary; Raveendra Gondhali (Wolters Kluwer Medknow Publications, 2016)
Background: Female sexual dysfunction (FSD) in Indian women is often overlooked due to cultural beliefs and considered as social taboos. Sexuality is an important and integral part of life. There are many causes of sexual dysfunction, but the prevalence of FSD in endometriotic patients is still underdiagnosed. Materials and Methods: Study design - Cross-sectional observational study conducted at tertiary care center, from June 2015 to March 2016. Sample size - Fifty-one patients in reproductive age group (18-47 years) who were diagnosed with endometriosis on diagnostic laparoscopy were included. Methods - FSD was assessed with a detailed 19-item female sexual function index questionnaire. All six domains of sexual dysfunction, i.e., desire, arousal, lubrication, orgasm, satisfaction, and pain were studied. Exclusion - Patients with other gynecological, medical or surgical history were excluded. Results: Out of 51 patients with endometriosis, 47.06% of patients had sexual dysfunction. With the increase in staging of endometriosis, sexual dysfunction prevalence is also rising. FSD was 100% in patients with severe endometriosis as compared to 33.33% in minimal endometriosis. Conclusion: Every individual deserves good sexual life. The sexual dysfunction associated with endometriosis should also be taken into consideration while managing these patients.